L’occhio cieco dell’Occidente: la logica narrativa dell’autoinganno - Scuderi, Attilio (L’ospite ingrato, 2025)
The narrative logic of deception requires transdisciplinary analysis tools, for a true science of lying actions, i.e. Pseudology. Within it, the sphere of self-deception, the ability to lie to oneself in order to lie to the world, is a central element of both the evolutionary and cultural dynamics of lying. Different knowledges contribute to this science: from social and anthropological sciences to ethology, from criminology to psychology and psychoanalysis. The study of the novel, the literary genre of mental and cultural modernity, becomes the litmus test of a debate that we continue to ignore; but that in times of heroism of self-deception is inevitable.